Surgical outcomes of a partial or total cystectomy for colorectal cancer invading the urinary bladder - Sakiko Nakamori; Kazushige Kawai; Akira Dejima; Soichiro Natsume; Ichiro Ise; Hiroki Kato; Misato Takao; Daisuke Nakano (Asian Journal of Surgery)
Background: Although a partial or total cystectomy may be performed for colorectal cancer (CRC) with bladder invasion, the indications for either procedure have not been established. The present study reports the oncological and functional outcomes of CRC in patients who underwent combined resection of the bladder and CRC via either a partial or total cystectomy. Methods: This retrospective study was conducted at a single center. A total of 107 consecutive patients with CRC who underwent colorectal surgery combined with partial or total cystectomy between January 2005 and August 2022 were enrolled. The short- and long-term outcomes of the surgery, especially postoperative bladder function, were assessed. Results: Ninety patients underwent partial resection and 17 patients underwent total resection. Forty-two patients (46.7 %) in the partial cystectomy group and 16 (94.1 %) in the total cystectomy group had histologically confirmed CRC with bladder invasion. The urinary-specific morbidity rate was 18.9 % in the partial cystectomy group and 15.6 % patients in the same group required treatment for dysuria at postoperative month 3. Of the patients who underwent partial cystectomy, five (5.6 %) experienced recurrence stemming from a bladder remnant. The cumulative distant recurrence rates did not differ significantly between patients who underwent partial cystectomy and those who underwent total cystectomy (41.9 % and 57.4 %, respectively). Conclusion: Partial bladder resection contributes to the preservation of bladder function and yields oncologically acceptable outcomes.